TILLERING AND LEAF AREA OF WINTER BARLEY EXPOSED TO SULPHUR DIOXIDE IN THE FIELD - Baker, C K (The New phytologist, 1987)
Winter barley (Hordeum vulgare L., cv. 'Igri'), grown as a crop in the field, was exposed to SO2 concentrations ranging from 40 to 200 ppb [parts per billion (109 ) by volume] above ambient. From spring onwards, plants at 40 and 50 ppb were consistently the heaviest, having slightly more tillers than plants in the other plots. In the range 80 to 200 ppb SO2 , the plants usually had fewer tillers than the controls, but this difference was not consistent throughout the season. Trends in the numbers and weights of tillers were interpreted as circumstantial evidence that 80 to 200 ppb of SO2 may have decreased assimilate production. Leaf area in May was markedly bigger in fumigated plants than in the controls. At 80 to 200 ppb the increases may have resulted from the plants having diverted a greater proportion of shoot dry weight into leaf tissue and from increased specific leaf area. These responses of 'Igri' barley in the field resembled those obtained by other workers for the same variety grown in controlled environments